2008
DOI: 10.1097/qai.0b013e3181893ef0
|View full text |Cite
|
Sign up to set email alerts
|

A Public Health Approach to Rapid Scale-Up of Antiretroviral Treatment in Malawi During 2004-2006

Abstract: In Malawi, a public health approach to ART increased treatment access and maintained high 6- and 12-month survival. Resource-limited countries scaling up ART programs may benefit from this approach of simplified clinical decision making, standardized ART regimens, nonphysician care, limited laboratory support, and centralized monitoring and evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 25 publications
2
46
0
Order By: Relevance
“…Importantly, NGO advocacy can exert eff ective pressure on policy makers to act on the evidence quickly. 15,[58][59][60] Health outcomes are often dependent on communitybased support systems, particularly for diseases such as tuberculosis and HIV. Thus, engaging with communities, including civil society organisations, 61 and where possible establishing community advisory boards to provide a link between researchers and the community, will probably help with research implementation as well as adoption of the results.…”
Section: Translation Of Research Results Into Actionmentioning
confidence: 99%
“…Importantly, NGO advocacy can exert eff ective pressure on policy makers to act on the evidence quickly. 15,[58][59][60] Health outcomes are often dependent on communitybased support systems, particularly for diseases such as tuberculosis and HIV. Thus, engaging with communities, including civil society organisations, 61 and where possible establishing community advisory boards to provide a link between researchers and the community, will probably help with research implementation as well as adoption of the results.…”
Section: Translation Of Research Results Into Actionmentioning
confidence: 99%
“…National programs [1013] have reported large-scale data of HIV treatment in both urban and rural populations [1417]; however, delivery of HIV treatment in some settings presents unique challenges and current ART delivery models may significantly limit the accessibility of ART. To have the greatest impact on public health, HIV treatment programs will have to be decentralized and integrated into the existing health care system.…”
Section: Introductionmentioning
confidence: 99%
“…Both observational and randomized controlled trials conducted in sub-Saharan Africa have shown that this simple intervention is associated with a substantial reduction in mortality among patients with HIV-associated TB (range, 19% to 46%) [40-44] (Table 4). This beneficial effect was observed in a range of settings with high or low rates of bacterial resistance to the drug and is additive in reducing early mortality when combined with ART [45]. …”
Section: Introductionmentioning
confidence: 99%